2022
DOI: 10.1590/0034-7167-2021-0278
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and cardiovascular risk factors in adolescents

Abstract: Objectives: to identify cardiovascular risk and cardiovascular risk factors in adolescents and verify correlations between these variables and biochemical markers, and between blood pressure percentiles, Body Mass Index, and biochemical markers. Methods: a cross-sectional study, conducted at a Brazilian school, from August to September 2019, including 205 participants who were interviewed. After the interview, anthropometric assessments, including weight, height, arm circumference, blood pressure checking, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Youth is an important period of life in which lifestyle habits are likely to be carried to further life stages, and a high prevalence of risk factors in adolescents is observed [ 1 , 2 , 3 ]. It was reported that parental behaviors, such as smoking, alcohol consumption and low physical activity level, were associated with higher cardiovascular risk factors in their children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth is an important period of life in which lifestyle habits are likely to be carried to further life stages, and a high prevalence of risk factors in adolescents is observed [ 1 , 2 , 3 ]. It was reported that parental behaviors, such as smoking, alcohol consumption and low physical activity level, were associated with higher cardiovascular risk factors in their children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%